The Impact of Point-of-Care Ultrasound on the Diagnosis and Management of Small Bowel Obstruction in the Emergency Department: A Retrospective Observational Single-Center Study - Carmine Cristiano Di Gioia; Alice Alame; Daniele Orso (Medicina)
Background and Objectives: Small bowel obstruction (SBO) requires prompt diagnosis and management. Due to its advantages, POCUS can be beneficial when assessing SBO. However, it is still doubtful whether POCUS performed by an emergency doctor can prolong the time of patients with SBO in the emergency department (ED). The primary outcome was time to diagnosis when using POCUS compared to not using it. Secondary outcomes included the processing time in the ED, ED length of stay (LOS), rates of abdominal radiography, hospital LOS, and mortality. Materials and Methods: We conducted a retrospective, observational study in our ED from 1 November 2021 to 31 December 2023, including patients aged 18 and older diagnosed with SBO. Both groups received confirmation of their diagnosis through contrast-enhanced computed tomography. The two groups of patients (POCUS group vs. non-POCUS group) were compared regarding the time needed to reach the final diagnosis (i.e., time to diagnosis), the ED LOS, the hospital LOS, and in-hospital mortality. Results: A total of 106 patients were included. The median time to diagnosis was 121 min for the POCUS group vs. 217 min for the non-POCUS group (p < 0.001). Median ED processing time was 276 min in the POCUS group compared to 376 min in the non-POCUS group (p = 0.006). ED LOS was also shorter in the POCUS group (333 vs. 436 min, p = 0.010). Abdominal X-ray rates were lower in the POCUS group (49% vs. 78%, p = 0.004). Hospital LOS was similar between the two groups (p = 1.000). Five non-POCUS patients died during hospitalization; none died in the POCUS group, but the difference was not statistically significant (p = 0.063). Conclusions: POCUS significantly reduced time to diagnosis and ED LOS. Further exploration is needed to assess long-term outcomes and the cost-effectiveness of integrating POCUS into ED practice.